Leading Integrasi Karakter Berpikir Plural Melalui Pendidikan Agama Islam di UPN Veteran Jatim - Taufikurrahman, Taufikurrahman; Sumbulah, Umi; Barizi, Ahmad; Dahri, Ahmad (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to develop a concept of plural thinking character which is integrated with an Islamic religious education approach both in practical and practical aspects. At UPN Veteran East Java, through strengthening the National Defense Character, the process of forming a plural thinking character can be analyzed. The diversity that exists at UPN Veteran Jatm certainly creates potential for intersections and gaps in both thought and action, but by forming a plural thinking character these intersections and gaps can be minimized and overcome. A qualitative approach was chosen in this research to look into literacy and other data sources that are closely related to research with the theme of integration of plural thinking characters. The meaning of leading will be answered with the perspective of various thoughts about pluralism. Good pluralism of religions, cultures, traditions and nations. Therefore, the result of this research is the concept of plural thinking character integration which is closely related to awareness of diversity, especially those built at UPN Verteran East Java.